A Zero‐Inflated Regression Model for Grouped Data1. (26th December 2014) - Brown, Sarah; Duncan, Alan; Harris, Mark N.; Roberts, Jennifer; Taylor, Karl
Abstract We introduce the (panel) zero‐inflated interval regression (ZIIR) model, which is ideally suited when data are in the form of groups, and there is an 'excess' of zero observations. We apply our new modelling framework to the analysis of visits to the general practitioner (GP) using individual‐level data from the British Household Panel Survey. The ZIIR model simultaneously estimates the probability of visiting the GP and the frequency of visits (defined by given numerical intervals in the data). The results show that different socio‐economic factors influence the probability of visiting the GP and the frequency of visits.